Proses Pembibitan serta Kelayakan Finansial Pembibitan Mangrove oleh Masyarakat dalam Upaya Pelestarian Lingkungan Pesisir - Ni Putu Sukanteri; I Gusti Ngurah Putu Yudi Darma Putra; I Ketut Arnawa (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study aims to determine the process of mangrove nurseries. To determine the benefits obtained for the community from producing mangrove nurseries in coastal environments, to determine the financial feasibility of weighting mangroves through empowering the surrounding community. The data analysis method used is qualitative descriptive analysis related to the flow or stages of the mangrove nursery business mechanism in the Suwung mangrove nursery and quantitative methodology in the form of business financial analysis on the Financial Feasibility of Mangrove Nursery Business in Efforts to Preserve the Coastal Environment. The mangrove nursery business includes several stages: location preparation and production facilities, providing planting media in polybags, making nursery beds, sorting mangrove fruit, planting mangrove fruit, and maintaining them until they become ready-to-plant seedlings. The benefits of the mangrove nursery process are physical and financial benefits for the community. The Suwung mangrove nursery shows economic feasibility. Namely, the Net Present Value (NPV) is obtained based on the results of calculating the respondent's mangrove nursery business, which is a positive value. The resulting Internal Rate of Return (IRR) of 31.24% indicates a higher return value than the prevailing bank interest rate. The Net Benefit Cost Ratio (Net B/C) obtained is 1.7 showing efficient implementation.